Towards a Better Understanding of the Informal Economy - Andrews, Dan (OECD Economics Department Working Papers, 2011)
It is important to understand the nature and drivers of informality, as its social and economic consequences are wide-ranging. This paper critically reviews the current state of cross-country research on informality and discusses how existing data sources can be more effectively employed and extended to shed light on the link between public policies and informality. A number of interesting findings emerge. The informal economy is multi-faceted and a wide range of definitions and measures are required to capture its diverse activities. However, most existing - and widely used - cross-country estimates of informality suffer from large measurement problems, which reduce the reliability of existing empirical evidence on the extent and drivers of informality. Accordingly, future research on informality should be closely linked to obtaining better data, particularly at the household and firm levels